2017
DOI: 10.1016/j.alcohol.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlation between alcohol preference and conditioned fear: Exploring a functional relationship

Abstract: Post-traumatic stress disorder (PTSD) and alcohol-use disorders have a high rate of co-occurrence, possibly because they are regulated by common genes. In support of this idea, mice selectively bred for high (HAP) alcohol preference show greater fear potentiated startle (FPS), a model for fear-related disorders such as PTSD, compared to mice selectively bred for low (LAP) alcohol preference. This positive genetic correlation between alcohol preference and FPS behavior suggests that the two traits may be functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Previous work has indicated that high alcohol-preferring mice exposed to cued fear conditioning and allowed free access to alcohol show enhanced hypervigilance in the fear-potentiated startle task, regardless of sex. However, fear conditioning only caused immediate increases in alcohol intake in male mice 58 . Another model using unpredictable chronic mild stress showed that an alcohol history plus stress increased binge drinking in male, but not female, mice 59 .…”
Section: Discussionmentioning
confidence: 91%
“…Previous work has indicated that high alcohol-preferring mice exposed to cued fear conditioning and allowed free access to alcohol show enhanced hypervigilance in the fear-potentiated startle task, regardless of sex. However, fear conditioning only caused immediate increases in alcohol intake in male mice 58 . Another model using unpredictable chronic mild stress showed that an alcohol history plus stress increased binge drinking in male, but not female, mice 59 .…”
Section: Discussionmentioning
confidence: 91%
“…Female rats show greater motivation to self-administer nicotine than male rats (Donny et al, 2000). Additionally, the heritability of smoking has been shown to be higher in women than in men (Pogun et al, 2017) and alcohol intake is higher in female HAP2 and LAP2 mice than in males (Chester and Weera, 2017; Oberlin et al, 2010); thus, the use of females might improve the detection of nicotine-alcohol interactive effects in HAP2 and LAP2 mice.…”
Section: Introductionmentioning
confidence: 99%